DEVELOPMENT OF A MUSHROOM HOUSE WITH A COMBINATION OF TECHNOLOGY - Suksawang, Watchara; Dumnil, Suchat; Wannakayont , Asada; Lonkunthosh , Nikom (Journal of MCU Nakhondhat, 2022)
The objectives of this paper are 1) to develop 2) to test the efficiency and 3) to assess the quality of the mushroom house by the combination of technology. The tools used include Mushroom nursery with a combination of technology Performance Test Table and Quality Assessment Form research method The researcher has developed a mushroom nursery. by applying the technological process to solve problems encountered in the mushroom cultivation process in the greenhouse by combining various technologies Then put it to test its performance. and assess the quality The basic statistics used are percentage, mean, and standard deviation. The results of the research were as follows: 1) The results of the development of a mushroom greenhouse by combining technology consisted of a house with dimensions 2 meters wide x 3 meters long x 2 meters high made of rust-proof painted steel. gable roof And there is an intelligent IOT technology system for spraying fog and ventilation for temperature control. and control the humidity inside the house to be suitable for mushroom cultivation in the house and a set of solenoid valves to control the fog sprayer Can work according to the specified temperature by controlling through the control cabinet. Automatic control and control via mobile applications The efficiency is 100%. 3) The results of the quality assessment of the mushroom house by the combination of technology. from the experts Overall, it was at the highest level, with a mean of 4.57 and a standard deviation of 0.49.